Draft animal power and its research in Ethiopia - Astatke, A.; Gebresenbet, G. (1998)
Animal traction in Ethiopia has been used since the third millennium B.C. Its use is confined to land preparation and seed covering using the traditional implement 'maresha' pulled mainly by a pair of oxen under a ridged neck yoke. Even though research to replace the 'maresha' and the multi-purpose use of animal power have been carried at different places of the country, its adoption were with little success. To feed the increasing population of the country and curtail the alarming land degradation, the traditional agricultural system has to change to a more productive one. The role of animal traction in this intensification process could be enormous. The present paper discusses the status of draft animal power and animal drawn implements in Ethiopia.